The Lingering Effects of Neighborhood Appraisal: Evaluating Redlining's Legacy in Pittsburgh - Rutan, Devin Q.; Glass, Michael R. (The Professional geographer, 2018)
Place-based classifications can create long-standing influences on neighborhood fortunes. Redlining is a classic example of these unintended effects. The Federal Home Loan Bank Board developed housing appraisal standards subsequently codified in Residential Security Maps. By georeferencing the 1937 map of Pittsburgh, we evaluated the spatial legacies of neighborhood appraisals. We identify persistent neighborhood conditions by comparing neighborhood evaluations with normalized census data from 1970 to 2000. Contemporary conditions correspond with security grades from the 1937 map. Concentrations of poverty, people of color, and vacancy persist in historically redlined areas. Concentrations of high incomes, home values, and homeownership persist elsewhere.